Nano-Channels Early Formation Investigation on Stainless Steel 316Ti after Immersion in Molten Pb-Bi - Rivai, Abu Khalid; Mardiyanto, Mardiyanto; Heinzel, Annette (Makara Journal of Technology, 2017)
Development of fuel cladding and structural materials in Pb-Bi environment, especially at high temperature, is a critical issue for the deployment of LFR (Lead alloy-cooled Fast Reactor) and ADS (Accelerator Driven Transmutation System). This is because of the corrosive characteristic of Pb-Bi to metals as constituent materials of fuel cladding and structural of the reactors. Corrosion test of a high-chromium austenitic stainless steel i.e. SS316Ti in molten Pb-Bi at 550 ºC has been carried out for about 300 hours continuously. The characterization using SEM-EDS (Scanning Electron Microscopy - Energy Dispersive X-ray Spectroscopy) showed that an iron oxide as the outer layer and a chromium oxide as the inner layer on the surface of the specimen were formed which in general have protected the steel specimen from corrosion and dissolution attack of Pb-Bi. However, small amount of Pb could penetrate into the iron oxide layer through ultra-narrow channels. Atomic Force Microscopy (AFM) with Electrostatic Force Microscopy (EFM) mode was employed to investigate the phenomena of the nano-channels early formation. The results of the nano-scale investigation showed clearly the formation of the channels at the early time of corrosion as the way of Pb to penetrate into iron oxide outer layer.